Fraud Pengadaan Barang dan Jasa Pemerintah Dengan Penerapan E-Procurement Sebagai Variabel Moderasi - Suci Melati; Anis Chariri (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
This study aims to analyze and obtain empirical evidence about the behavior of government procurement of goods and services fraud with intentions, attitudes, subjective norms, and behavioral control as predictor variables and e-procurement implementation as moderating variables. Respondents who became the object of this study were employees who were involved in the procurement of goods and services in a government agency. This research is a cross-sectional study by distributing data using a questionnaire. Questionnaires were returned and processed by as many as 478 respondents. Data analysis using the Structural Equation Model-Partial Least Squares (SEM-PLS. The results showed that statistically intention has a positive effect on procurement fraud, subjective norms, and perceived behavioral control have a positive effect on intention. Meanwhile, attitude does not positively affect intentions, and implementation of e-procurement does not weaken the relationship between intention and procurement fraud